2017
DOI: 10.18203/2320-1770.ijrcog20171939
|View full text |Cite
|
Sign up to set email alerts
|

Day-2 serum progesterone level and IVF/ICSI outcome: a comparative study

Abstract: Background: Purpose of this study was to evaluate the in vitro fertilisation outcome in patients having normal or elevated day-2 serum progesterone level undergone IVF by using GnRH antagonist.Methods: A retrospective study conducted in Institute of Reproductive Medicine, Chennai during January 2013 to March 2014. According to patient’s Day-2 serum progesterone level the total no of cases (N=151) were divided into two groups group-1 (N=116) with progesterone value ≤1.5ng/ml and group-2 (N=35) with progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The day-2 serum progesterone has been estimated as a key hormone in predicting the ART outcome. Studies suggest that a high value of day-2 serum progesterone level was associated with a lower clinical pregnancy rate (Mahapatro and Radhakrishan, 2017). Likewise, other authors found the same result in IVF cycles using the GnRH antagonist protocol (Kolibianakis et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…The day-2 serum progesterone has been estimated as a key hormone in predicting the ART outcome. Studies suggest that a high value of day-2 serum progesterone level was associated with a lower clinical pregnancy rate (Mahapatro and Radhakrishan, 2017). Likewise, other authors found the same result in IVF cycles using the GnRH antagonist protocol (Kolibianakis et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…Fresh ovarian stimulation cycle with ET i. At basal follicular phase Three studies 3,12,13 reported progesterone monitoring in this category. Serum progesterone was measured on day 2 of the menstrual cycle.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two thresholds were identi ed, P>0.65ng/ml and P>1.5ng/ml. Two studies reported using D3 embryos 3,12 and one study reported both D3 and D5 embryos 13 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation